Causes of admission and mortality among patients admitted in 37 cardiology departments in 17 Sub-Saharan African countries: the FEBRUARY observatory (2016–2021) from African Research Network. (3rd October 2022) - Ali Toure, I; Traore, A K; Cavagna, P; Damorou, J M; Diao, M; Dzudie, A; N'Guetta, R; Kouam Kouam, C; Hermann, Y; Limbole, E; Gaye, B; Toure, C; et al.
Abstract: Background: Cardiovascular disease (CVD) is a major cause of death worldwide. At least two-third of CVD death occurs in low- (LIC) and middle-income (MIC) countries. An estimated 1 million deaths were attributable to CVD in sub-Saharan Africa (SSA) alone. Scarce data are available about the admission for CVD and outcome in cardiology department in SSA. Purpose: To describe admission for CVD and outcome of hospitalization in 17 in SSA countries. Methods: We conducted a transversal and longitudinal study in CV department of 37 hospitals from 23 cities in 17 SSA countries (10 low income: Niger, Guinea, Benin, Mali, Democratic Republic of the Congo, Tchad, Burkina Faso, Togo, Burundi, Ethiopia and 7 middle income: Cote d'Ivoire, Senegal, Cameroon, Congo, Soudan, Mauritania, Gabon). The February study was designed by a multidisciplinary collaborative team of epidemiologists, pharmacists and cardiologists from Africa and France. This ongoing observatory included all inpatients in February from each year since 2016.Data including socio-demographic and clinical characteristics, causes of admission, clinical, biological, complementary examinations, treatments, length of stay and discharge diagnosis were collected by the investigating physicians. All analyses were performed through scripts developed in the R software (4.0.3 (2020-10-10)) Results: Overall, 4360 patients were included in the February study. Men represented 56.4%. Mean of age was 56.7±16.8 years. The main cause of admission was heart failure (41.5%) followed by acute coronary syndrome (11.9%) and stroke (11%). Cause of admission varied significantly across countries (p<0.01) and over the years (p<0.01). Proportions of admission for heart failure varied from 20% in Ethiopia to 62% in Guinea. Mean of length of stay was 9.95±22.4 days. All causes of admission confounded, in-hospital mortality rate was 11% (N=423). Mortality rate differed significantly according to causes of admission (p<0.01).Mortality rate among patients admitted for stroke, heart failure and acute coronary syndrome was respectively 18%, 12.3% and 9.5%. Overall, 31 (0.7%) were admitted for endocarditis and mortality rate among them was 20.8% (figure). Overall, mortality rate did not vary according to gender or over the years but was significantly different according to patient wealth index (p<0.05), countries (p<0.01) and level income countries (p<0.01). Mortality rate was significantly higher in LIC. Conclusion: Heart failure, acute coronary syndrome and stroke represent the two-third of causes of admission. Overall, mortality rate in cardiology departments in SSA reached 11%. Funding Acknowledgement: Type of funding sources: None.